Domas (Dompet Masker) Sebagai Inovasi Pemanfaatan Limbah Plastik dan Kain Perca Bermotif Keanekaragaman Indonesia di Era Pandemic COVID-19 - Ella Ardini; Eka Kristin Ellisabeth; Fajar Ferdianto; Tri Wahyuni Ismoyowati (Jurnal Pengabdian Masyarakat - PIMAS, 2022)
Background: One of the efforts funded by Dikti in implementing the Student Creativity Program in the field of entrepreneurship gave us the opportunity to produce a Dompet Mask (DOMAS) product made using modified patchwork waste and mica polyvinyl chloride plastic waste with a thickness of 0.4 mm. The tools and materials we use are very affordable during this COVID-19 pandemic. Objective: Provide quality Domas innovation, practical, and safety of the waste material. Providing business opportunities through student creativity programs. Marketing DOMAS offline and online throughout Indonesia by actively promoting and improving the quality of products handmade. Methods: The implementation of activities is carried out outside the network (offline) and within the network (online). The activity was carried out at the production house located at Jatisawit Housing, Sleman, Yogyakarta. The production period starts on 08/08/2021 until 12/09/2021. Product marketing online and offline. Result: The selling price per unit is Rp. 20,000. For five weeks producing 250 DOMAS. DOMAS sales resulted in a profit of Rp. 3,000,000 with a cost of Rp. 1,549,080, a profit of Rp. 418,200 was obtained. The number of DOMAS that have been sold is 150 units. The profit per DOMAS unit is IDR 2,788. The original price per wallet is Rp. 17,212. Conclusion: The "DOMAS" mask wallet is a new breakthrough in the era of the COVID-19 pandemic. DOMAS has the advantage of being able to store clean and dirty masks in one place. In addition to the unique and attractive design of the mask, the materials used are also environmentally friendly, made from plastic waste mica PVC and waste batik patchwork with the motifs of the diversity of the archipelago.